Effects of the pan-caspase inhibitor Q-VD-OPh on human neutrophil lifespan and function - Lisa Khuu; Alisha Pillay; Allan Prichard; Lee-Ann H. Allen (PLoS ONE, 2025)
Human neutrophils are abundant, short-lived leukocytes that turn over at a rate of approximately 1011 cells/day via a constitutive apoptosis program. Certain growth factors, inflammatory mediators and infectious agents can delay apoptosis or induce neutrophils to die by other mechanisms. Nonetheless, a large body of data demonstrates that apoptosis of untreated neutrophils typically ensues within 24 hours of cell isolation and in vitro culture. At the molecular level apoptosis is driven by executioner caspase-3, and during this process cell proinflammatory capacity and host defense functions are downregulated. We undertook the current study to determine the extent to which human neutrophil viability and function could be prolonged by treatment with the non-toxic, irreversible, pan-caspase inhibitor Q-VD-OPh. Our data demonstrate that a single 10 μM dose of this drug was sufficient to markedly prolong cell lifespan. Specifically, we show that apoptosis was prevented for at least 5 days as indicated by analysis of nuclear morphology, DNA fragmentation, and phosphatidylserine externalization together with measurements of procaspase-3 processing and caspase activity. Conversely, mitochondrial depolarization declined despite abundant Myeloid Cell Leukemia 1 (MCL-1). At the same time, glutathione levels were maintained and Q-VD-OPh prevented age-associated increases mitochondrial oxidative stress. Regarding functional capacity, we show that phagocytosis, NADPH oxidase activity, chemotaxis, and degranulation were maintained following Q-VD-OPh treatment, albeit to somewhat different extents. Thus, a single 10 μM dose of Q-VD-OPh can sustain human neutrophil viability and function for at least 5 days.